Implicit learning in children with and without developmental coordination disorder. - Candler C; Meeuwsen H (American Journal of Occupational Therapy)
OBJECTIVE: The ability to use perceptual cues within the environment to guide movement accurately can be acquired implicitly in that skill may increase while the learner is not consciously aware of what cues are being used. In this study, the implicit learning capabilities of children with and without developmental coordination disorder were compared. METHOD: Twenty-two children (11 with developmental coordination disorder, 11 without the disorder) played a computer game where they 'caught' a descending ball image with a paddle on the screen. The dependent variable was accuracy of catch, as measured by the score on the computer game. On training trials, a visual cue appeared 50% of the time that signaled the direction of the ball. On probe trials, the visual cue was false. After completing the task, the children were interviewed about their conscious awareness of the cue. A mixed factorial analysis of variance (ANOVA) was used to analyze the data for group comparisons. RESULTS: Of the 22 children, only 6 indicated that they were aware of the cue. A mixed factorial ANOVA was significant for greater error when the visual cue was false, F(11.12, 22.49) = 27.27, p = .000, indicating that the children responded to the cue. No difference was found between groups in game performance. CONCLUSION: Children with developmental coordination disorder in this study were able to implicitly recognize and use a perceptual cue to enhance their performance on a computer game. Strategies that foster implicit learning may be relevant to occupational therapy intervention.